Academics tap The Wire to stimulate social debate. - Gill, John (Times Higher Education, 2009)
The article focuses on the concepts depicted in the social science fiction television series "The Wire" which has made it the subject of a study during a conference to be held at the University of York, England on November 26-27, 2009. It says that the series has attracted several debates, papers and theses on sociology, economy and political science because of its theme on diverse issues such as school systems, the impact of dying industries on communities and the parallelism between life on the streets of Baltimore and certain parts of Great Britain.